Private security companies during the Iraq War military performance and the use of deadly force - Fitzsimmons, Scott (Cass military studies, 2016)
The work focuses on and compares the activities of the US companies Blackwater and Dyncorp. Despite sharing several important characteristics, such as working for the same client (the US State Department) during the same time period, the employees of Blackwater fired their weapons far more often, and killed and seriously injured far more people in Iraq than their counterparts in DynCorp. This book will be of much interest to students of the Iraq War, Private Security Companies, Military Studies, War and Conflict Studies and IR in general.